THE RELATIONSHIP BETWEEN STUDENTS' PERCEPTIONS OF TEACHER BEHAVIOR ON BEHAVIORISTIC THEORY AND CREATIVITY WITH THE SOCIAL COMPETENCE OF MADRASAH TEACHERS IN AGAM REGENCY - Zet Donny; Ridwan Ridwan; Zaimar Zaimar; Zelhendri Zen (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This research aims to determine the "Relationship between Student Perceptions of Teacher Behavior and Behaviorist Theory and Creativity with the Social Competence of State Madrasah Tsanawiyah Teachers in Agam Regency". This type of research is quantitative research, namely research that focuses on studying objective phenomena to be studied quantitatively. The research sample will be chosen randomly. Data were analyzed using SPSS 16.0 for Windows. The research results show that: (1) There is a correlation between students' perceptions of teacher behavior regarding behaviorist theory and teacher competence at MTsN in Agam Regency, which is declared to be proven to be true with a strong correlation level. (2) there is a correlation between students' perceptions of creativity and teacher competence at MTsN in Agam Regency which has been proven to be true with a moderate level of correlation. (3) The results of the analysis show that the null hypothesis (H0) is rejected and the alternative hypothesis (H1) which states that there is a significant relationship between students' perceptions of teacher behavior towards behavioristic theory and creativity together with teacher competence at MTsN in Agam Regency is accepted and proven to be true.